KUALITAS PELAYANAN SEBAGAI KUNCI KEPUASAN DAN KEPERCAYAAN PASIEN RAWAT INAP - Yulfikasari Yulfikasari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to analyze the effect of service quality on inpatient satisfaction and trust at Dr. Sumantri Level IV Hospital in Parepare, South Sulawesi. A quantitative approach with a survey design was employed. The participants consisted of 87 inpatients selected based on predefined inclusion criteria. Data were collected using a structured questionnaire that met validity and reliability requirements. Data analysis was conducted using stepwise logistic regression to identify service quality dimensions that significantly influence patient satisfaction and trust. The results indicate that not all service quality dimensions contribute equally to patient satisfaction and trust. After model refinement, responsiveness and assurance emerged as significant predictors, with assurance demonstrating a more dominant effect. These findings indicate that inpatient satisfaction and trust are primarily shaped by the ability of healthcare providers to respond promptly to patient needs and to deliver services that ensure safety, professionalism, and certainty. This study provides empirical contributions to the literature on health service quality management, particularly in the context of regional referral hospitals, and offers practical implications for hospital management in developing service quality improvement strategies that emphasize patient experience and trust. Keywords: Service Quality, Patient Satisfaction, Patient Trust, Inpatient Care, Hospital